Evaluation of the Relationship Between Cranial Magnetic Resonance Imaging and Epileptic Features in Tuberous Sclerosis Complex - Kılıç, Hüseyin; Karaman, Ahmet Kürşat; Mavi, Deniz; Yüksel Karatoprak, Elif; Korkmazer, Bora; Kızılkılıç, Osman; Saltık, Sema (Cerrahpaşa Medical Journal, 2021)
Objective: Tuberous sclerosis complex is an inherited neurocutaneous disease that is characterized by pleomorphic features involving many organ systems, especially the brain. Neurological involvement occurs in approximately 90% of patients with tuberous sclerosis complex and includes epilepsy, intellectual disability, and autism. The aim of this study is to investigate the relationship between epileptic seizures and electroencephalographic features and neuroradiological findings in patients with tuberous sclerosis complex. Methods: In this study, 29 patients who were followed up in the outpatient clinic were included. Clinical, demographic, and laboratory data of the patients were analyzed retrospectively from patient files and computer database. Data analyzed included demographic features, neuroimaging findings; electroencephalographic findings, and seizure history. The relationship between tuberous sclerosis complex- specific brain magnetic resonance imaging findings and features of epileptic seizures was compared. Results: The median age of our patients was 8.5 years (range: 1.7-17.3), and female (n = 9) to male (n = 20) ratio was 1:2.2. Significant correlation was found between the total number of cortical tubers detected by brain magnetic resonance imaging and (1) onset of seizures under 1 year old (P = .044) and (2) drug-resistant epilepsy (P = .03). The examination of clinical and electroencephalographic features of the patients revealed hypsarrhythmia in any electroencephalography in 11 patients (37.9%), first seizure under 1-year-old in 20 patients (69%), 19 (65.5%) patients with seizures in the past year, drug-resistant epilepsy in 12 patients (41.4%), and status epilepticus in 6 patients (20.7%). Conclusion: In this study, we tried to reveal the brain magnetic resonance imaging findings and clinical features of patients with tuberous sclerosis complex, which were observed to cause serious neurological complications. Cite this article as: Kılıç H, Kürşat Karaman A, Mavi D, et al. Evaluation of the relationship between cranial magnetic resonance imaging and epileptic features in tuberous sclerosis complex. Cerrahpaşa Med J. 2021;45(3):205-209.